Hubungan Peran Pengawas Minum Obat oleh Keluarga dengan Petugas Kesehatan Terhadap Pengetahuan, Perilaku Pencegahan, dan Kepatuhan Klien TBC dalam Konteks Keperawatan Komunitas di Kabupaten Wonosobo - Istiawan, Rochani; Sahar, Junaiti; Bachtiar, Adang (Jurusan Keperawatan FIKES UNSOED, 2006)
The program of TB drug observer should be increased the TB client in adherence, but the national number of the negative result of Tuberculosis diagnostic still below the national target (80%). The goal of this study was to know the correlation between TB Drug Observer by the Family and Health Worker with the Knowledge, Behavior and Adherence of TB patient. This study was used descriptive correlation design with cross sectional approach. The total sample of this study where that matches with the inclusive criteria were 72 TB patients. The instruments were self prepared by the researcher with validity test (counted r>tabled r=0.361) and the reliability test with a=0.9298 (TB drug observer role), a=0.9076 (knowledge), a=0.8067 (prevention behavior), a=0.6631 (adherence). Product Moment Pearson’s Correlation Coefficient was used to analyze the correlation between TB Drug Observer by the Family and Health Worker with the Knowledge, Behavior and the Adherence of TB patient. The result of this study showed a strong correlation between the family TB Drug Observer to the prevention Behavior (r=0.656) in positive pattern. The significant correlation family TB Drug Observer to the prevention TB behavior (p=0.0001). Another result showed a strong correlation between health workers TB Drug Observer to the knowledge of the patient (r=0.706) in positive pattern. Also the result showed a strong correlation between health workers TB Drug Observer to the prevention TB behavior (r=0.673) in positive pattern. And there was a mild correlation also between health workers TB Drug Observer to the adherence of TB medication (r=0.553) in positive pattern. There was also a significant correlation between health workers TB Drug Observer role to the knowledge, TB prevention behavior and TB medication adherence. Confounding variables were not have correlation to the family TB Drug control Adherence Observer role to the knowledge, TB prevention behavior and TB medication. The conclusion from this study showed a strong correlation between family TB drug observer and the prevention behavior, and a strong correlation between health worker TB drug observer and the knowledge, prevention behavior and adherence of the patient. This study suggested that the community nurse should keep visit the family to observe and maintain the prevention behavior and adherence to the TB medication program.